Monovalent Salt Dependence of the Bacterial RNA Polymerase Open Complex Dynamics - Bera, Subhas Chandra; Seifert, Mona; Ostrofet, Eugeniu; Spermann, Monika; Papini, Flavia Stal; Malinen, Anssi M.; Dulin, David (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

Quantitative parameters of bacterial RNA polymerase open-complex formation, stabilization and disruption on a consensus promoter - Bera, Subhas Chandra; America, Pim P. B.; Maatsola, Santeri; Seifert, Mona; Ostrofet, Eugeniu; Cnossen, Jelmer; Spermann, Monika; Stal Papini, Flavia; Depken, Martin; Malinen, Anssi M.; Dulin, David (Nucleic Acids Research, 2022)
Transcription initiation is the first step in gene expression, and is therefore strongly regulated in all domains of life. The RNA polymerase (RNAP) first associates with the initiation factor sigma to form a holoenzyme, which binds, bends and opens the promoter in a succession of reversible states. These states are critical for transcription regulation, but remain poorly understood. Here, we addressed the mechanism of open complex formation by monitoring its assembly/disassembly kinetics on individual consensus lacUV5 promoters using high-throughput single-molecule magnetic tweezers. We probed the key protein-DNA interactions governing the open-complex formation and dissociation pathway by modulating the dynamics at different concentrations of monovalent salts and varying temperatures. Consistent with ensemble studies, we observed that RNAP-promoter open (RPO) complex is a stable, slowly reversible state that is preceded by a kinetically significant open intermediate (RPI), from which the holoenzyme dissociates. A strong anion concentration and type dependence indicates that the RPO stabilization may involve sequence-independent interactions between the DNA and the holoenzyme, driven by a non-Coulombic effect consistent with the non-template DNA strand interacting with sigma and the RNAP beta subunit. The temperature dependence provides the energy scale of open-complex formation and further supports the existence of additional intermediates.
CRIS-Team WoS Importer:2022-07-22